The Insistence of Art Philosophy and Aesthetics after Early Modernity - Kottman, Paul A. (Fordham University Press, 2016)
The essays in 'The Insistence of Art' suggest ways in which the artworks and practices of the early modern period show the essentiality of aesthetic experience for philosophical reflection, and in particular for the rise of aesthetics as a philosophical discipline, while also showing art's need for philosophy.